Agriculture 4.0 - The Future of Farming Technology - Parras-Burgos, Dolores; Molina Martínez, José Miguel; García-Mateos, Ginés (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The agricultural sector is undergoing a profound transformation derived from the introduction of new technologies and tools from industry 4.0, giving rise to what has been called Agriculture 4.0. This Reprint contains a selection of some interesting recent advances in this field, including new techniques for remote crop sensing and agricultural machinery, the development of novel vision and deep learning algorithms, advances in aquaculture technologies, and a review on the state of the art in Horticulture 4.0.